c-fos mRNA expression in macrophages is downregulated by interferon-gamma at the posttranscriptional level. - Radzioch, D (1991)
Treatment of macrophages with interferon-gamma (IFN gamma) strongly decreased the induction of c-fos mRNA by 12-O-tetradecanoylphorbol-13-acetate (TPA), lipopolysaccharide, or calcium ionophore A23187 in macrophages. Under the same experimental conditions, IFN gamma induced oligo(A) synthetase mRNA and did not affect the constitutive expression of transforming growth factor beta mRNA, indicating that IFN gamma did not induce general degradation of mRNAs. Run-on experiments indicated that c-fos was constitutively transcribed at low levels and that TPA augmented c-fos transcription. IFN gamma did not inhibit constitutive or TPA-induced c-fos transcription. However, IFN gamma decreased c-fos mRNA stability, as assessed by measuring the half-life of c-fos mRNA in actinomycin D-treated cells. These results indicated that IFN gamma inhibited c-fos mRNA induction by TPA at the posttranscriptional level.